INTERFERENSI MORFOLOGI BAHASA JAWA DALAM BAHASA INDONESIA OLEH MASYARAKAT TUTUR KOTA MOJOKERTO - Ramadhani, Muhammad Rizal (Universitas Islam Sumatera Utara, 2023)
This research aims to describe morphological interference and the factors that cause morphological interference. The subject in this research is a speech communties in Rajekwesi Street RT 02 RW 07 Mojokerto City. This research approach is theoritical and metodological approach. Theoritical approach are using in this research is a sociolinguistic, while method in this research is a qualitative descriptive approach. The data obtain from listening and note technique on data card. Analysis data in this research is a matching method. The result in this research consist of Javanese morphological interference which form (a) prefix n-, m-, ny-, nge-, and ke-, (b) infix -em-, and -er-,(c) sufix -en, -an, -ne, and -no, (d) confix n – i, diper – no, ke – an, ng – no, nge – i, and di – no. There are two factors that cause morphological interference in this study, the loss of morphemes and the bilingualism of the speech participants.